The Establishment of the Bolshevik Occupation Regime in Eastern Galicia, Volyn, Northern Bukovyna and Bessarabia in 1939-1953 as a Form of Sovietization - Михайло Юрій (Науковий вісник Чернівецького національного університету імені Юрія Федьковича. Історія)
According to rough calculations, the Soviet authorities repressed 3-4 times more people than the Nazis in the German occupation zone, where the population was almost twice as large as in the territories annexed to the USSR. The large-scale repressions of Stalinism had all the signs of being classified as a crime against humanity under international law. The unification of Ukrainian lands within the Ukrainian SSR is assessed ambiguously. After the events of September 1939 and June 1940, the western Ukrainian lands of Northern Bukovyna and Bessarabia joined Soviet Ukraine. Politicians and historians of that time assessed this fact as the fulfillment of the eternal dream of many generations of Ukrainians to reunify in a single Ukrainian SSR. The arrival of the Red Army was interpreted by them as «liberating». From today’s point of view, two opposite historical events merged in these fields: on the one hand, the realization of Ukrainians’ aspirations for the concentration of all ethnic Ukrainian lands in a single state; on the other – brutal disregard for the norms of international law, undisguised aggression, which was met with an unfavorable attitude from the Western states. The forced integration of Western Ukraine, Northern Bukovyna, and Bessarabia into the system of «barrack socialism» that prevailed in the USSR was accompanied by unprecedented repression, violations of laws and human rights, and deep social, economic, and spiritual deformations. Starting from the end of 1939, at first slowly, and then with increasing speed, at the end of 1940 and further in the first half of 1941, the flywheel of terror was spun, which became especially brutal in the second stage of Sovietization after the expulsion of the fascist troops, which led to the full Sovietization of the annexed regions. For the first time in several centuries, Ukrainians found themselves within the borders of one state, but the repressive regime convinced most Western Ukrainians that the future did not lay in such a union, but in the creation of an independent, united Ukrainian state. Apparently, with this in mind, the prominent Ukrainian artist O. Dovzhenko noted in his diary in 1942: «Ah, if I had enough strength and time, I would write a novel about the liberation of Western Ukraine, about the reunification of our peoples... And as Ukrainian people, I actually had nothing to do with it...».